PENGARUH PENERAPAN METODE PROJECT BASED LEARNING (PjBL) PADA MATERI UJI KUALITATIF OBAT - ULUTIAH AAN HIKMAH, HU'UL; NIKMAH, AAN (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2024)
The subject of Pharmaceutical Chemistry is often considered difficult for students to understand. Therefore, an innovative learning method is needed that can connect the material with real-world objects and produce projects in the learning process, one of which is through the implementation of the Project-Based Learning (PjBL) method. This study aims to examine whether the PjBL method can enhance students' science process skills in the topic of